Development of chitosan films containing β-cyclodextrin inclusion complex for controlled release of bioactives. (July 2020) - Zarandona, I.; Barba, C.; Guerrero, P.; de la Caba, K.; Maté, J.
Abstract: 2-phenyl ethanol is a natural compound, which have many applications due to its nice fragrance, bacteriostatic and antifungal character. However, it is difficult to keep it stable and it is highly volatile. In this work, chitosan films with 2-phenyl ethanol were developed and inclusion complexes with cyclodextrins (CDs) were prepared in order to have a controlled release of 2-phenyl ethanol. β-CD was selected to develop the inclusion complex since it showed higher retention yield (45%, molar basis) than α- or γ-CDs. Chitosan films incorporated with β-CD:2-phenyl ethanol were homogeneous, transparent and colorless, and showed high mechanical resistance. Furthermore, the release results of the films without the inclusion complex indicated that 2-phenyl ethanol was evaporated during the film preparation, and only an 8% of the total bioactive was retained in the film, while more than 90% of 2-phenyl ethanol was retained in the films with the inclusion complex. Graphical abstract: Image 1 Highlights: Cyclodextrins (CDs) formed inclusion complexes with 2-phenyl ethanol. β-CDs showed higher retention yield than α- or γ-CDs. Films with β-CD:2-phenyl ethanol were homogeneous, transparent and colorless. Tensile strength of chitosan films reached values up to 48 MPa. Films with inclusion complex preserved the bioactive inside the inclusion complex.